Omskrivningarnas Odyssé. Feministiska omskrivningar av grekiska myter – en genre i förändring - Björkman,Hedvig (2022)
This bachelor’s thesis in publishing science examines the paratextual marketing of feminist retellings of Greek myths, and how it has developed from the year 2005 through 2022. Feminist retellings is a genre that has become a trend in recent years, with massive bestsellers such as Madeline Miller’s Circe, which was published in 2018, spearheading the trend. Before there was Miller however, there was Margaret Atwood’s The Penelopiad in 2005; but despite its status as a critically acclaimed bestseller, it did not launch A thousand ships or similar bandwagon books. The aim of this thesis is to examine how the trend of feminist retellings have developed since 2005, what traits marks the genre and how they developed, as well as why feminist retellings has become a trend. Feminist retellings provide a case study of the bestseller phenomena, feminist bestsellers, and how trends can develop genres. This study examined 18 different English feminist retellings of Greek myths that have been published since 2005, with a focus on their book covers, which have been the basis for a qualitative, comparative, paratextual analysis. The results found that feminist retellings did not develop unique genre-signifiers until the release of Circe in 2018, which then provided the base for the paratexts of subsequent covers and published titles. The results also showed that feminism was not part of the marketing of titles published before 2018, which shows that the works published before 2018 are only considered feminist retellings in retrospect. Indeed, the genre of feminist retellings of Greek myths can only be called a genre, rather than a trend, if titles can be considered feminist in retrospect. In general, the wish to find works considered feminist retellings seems to come from readers’ desire to examine the patriarchal literary tradition, and to “give a voice” to previously silent women, in the wake of the #metoo movement. This speaks to current social and political trends’ power to affect literature, as well as large publishing companies’ profit-orientated motives for publishing – and classifying works as – specifically feminist retellings, rather than simply retellings.
Keywords: Feminist literature; Feminist bestsellers; Bestsellers; Genre; Marketing; Publishing science; Greek mythology; Anglo-American; Book covers; Paratexts; Paratextual analysis; Retellings